2018
DOI: 10.1002/mgg3.394
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four TMC1 variations in different Chinese families with hereditary hearing loss

Abstract: BackgroundVariants in TMC1 (transmembrane channel‐like 1) can cause both autosomal dominant and recessive hearing loss in human population. Mice with Tmc1 variants have been shown to be ideal animal models for gene therapy. In this article, we report four TMC1 variants in four different Chinese families and the follow‐up auditory phenotype of a previously reported family.MethodsFour families with TMC1 variants, as well as a previously described family with TMC1 variant orthologous to the Beethoven mouse, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…A previously described dominant mouse mutation, Tmc1 p.M412K ( Beethoven ), leads to early hearing loss and hair cell degeneration ( Vreugde et al, 2002 ). The homologous human deafness mutation is TMC1 p.M418K ( Zhao et al, 2014b ; Wang et al, 2018 ), the mutation site is adjacent to two other missense mutations causing deafness: TMC1 p.L416R ( Chen et al, 2015 ) and TMC1 p.G417R ( Yang et al, 2010 ). Here we report a fourth deafness mutation in the same region, TMC1 p.T422K and we generate and characterize the homologous mouse mutation Tmc1 p.T416K.…”
Section: Introductionmentioning
confidence: 99%
“…A previously described dominant mouse mutation, Tmc1 p.M412K ( Beethoven ), leads to early hearing loss and hair cell degeneration ( Vreugde et al, 2002 ). The homologous human deafness mutation is TMC1 p.M418K ( Zhao et al, 2014b ; Wang et al, 2018 ), the mutation site is adjacent to two other missense mutations causing deafness: TMC1 p.L416R ( Chen et al, 2015 ) and TMC1 p.G417R ( Yang et al, 2010 ). Here we report a fourth deafness mutation in the same region, TMC1 p.T422K and we generate and characterize the homologous mouse mutation Tmc1 p.T416K.…”
Section: Introductionmentioning
confidence: 99%
“…These two mutations were not detected in 200 Chinese Han normal-hearing controls and are not present in 1000 Genomes and ExAC databases. The p.R34X mutation with minor allele frequency (MAF) of 0.0002 in ExAC has been previously detected in many patients from Pakistan, Iran, Turkey, and Tunisia but is relatively rare in China [ 16 , 27 – 29 ]. On the other hand, while the p.M413T mutation is novel.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that mutations in TMC1 may cause both prelingual profound autosomal recessive deafness DFNB7/11 and postlingual progressive autosomal dominant deafness DFNA36 [13]. To date, more than 60 mutations in TMC1 are reported worldwide [15], with the recessive mutations predominantly associated with prelingual severe-to-profound hearing loss [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…8,16 In human TMC1 deafness (DFNA36), although HL is severe to profound by 60 years of age, its onset varies from 5 to 28 years. 4,5 Because deterioration of HL is much slower in humans than in Tmc1 Bth/+ mice, there may be a greater temporal window for successful therapeutic intervention, which could allow for rescue of the mid to high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Bth mice carry a dominant-negative missense mutation, c.1235T > A (p.Met412Lys), in the transmembrane channel-like gene 1 (Tmc1) gene 3 that is orthologous to the c.1253T > A (p.Met418Lys) variant reported in human TMC1 in two Chinese families segregating early-onset progressive HL. 4,5 The progression of HL in Bth-heterozygous mice (Tmc1 Bth/+ ) is reflected by degeneration of cochlear inner hair cells (IHCs) in a base-to-apex gradient ( Figure 1A). Outer hair cells (OHCs) remain intact in a middle-to-apical region for at least the first 20 weeks of life.…”
Section: Introductionmentioning
confidence: 99%